2017
DOI: 10.1021/acs.langmuir.7b00578
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds as Nucleating Agents for Protein Crystallization

Abstract: Nanodiamond (ND) is a carbon-based nanomaterial with potential for a wide range of biological applications. One of such applications is to facilitate the nucleation of protein crystals in aqueous solution. Here, we show that NDs (nominal diameters of 30 and 100 nm) after surface oxidation in air and subsequent treatment in strong acids are useful as heterogeneous nucleating agents for protein crystallization. Tested with lysozyme, ribonuclease A, proteinase K, and catalase, the nanomaterials in either aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…It has been shown that the structural and chemical properties of both nanoparticles and proteins along with the degree of the interaction between them play key roles in regulating such surface-driven modifications in the native protein structures . Furthermore, in a complex nanoparticle–protein system, the presence of nanoparticles may control the interaction between protein molecules as well as their enzymatic activity and protein delivery. ,, On the other hand, it is also possible that the interaction of proteins can alter the surface properties and colloidal stability of the nanoparticles. , Proteins may influence the various phase transformations in the nanoparticles, for example, gelation, crystallization, glass transition, and flocculation, which can be used to prepare multifunctional materials. ,, In addition to these, the protein corona has also been shown to influence several other properties of the nanoparticle system such as degradation, accumulation, clearance, inflammation, and cellular uptake. , The most important aspect of the nanoparticle–protein interaction is that it can modify the biophysical properties of the nanoparticles, which often differ significantly from those of the bare nanoparticles . The protein adsorption on nanoparticles confers a new biological identity to the biological milieu, which subsequently controls the biological response of the nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the structural and chemical properties of both nanoparticles and proteins along with the degree of the interaction between them play key roles in regulating such surface-driven modifications in the native protein structures . Furthermore, in a complex nanoparticle–protein system, the presence of nanoparticles may control the interaction between protein molecules as well as their enzymatic activity and protein delivery. ,, On the other hand, it is also possible that the interaction of proteins can alter the surface properties and colloidal stability of the nanoparticles. , Proteins may influence the various phase transformations in the nanoparticles, for example, gelation, crystallization, glass transition, and flocculation, which can be used to prepare multifunctional materials. ,, In addition to these, the protein corona has also been shown to influence several other properties of the nanoparticle system such as degradation, accumulation, clearance, inflammation, and cellular uptake. , The most important aspect of the nanoparticle–protein interaction is that it can modify the biophysical properties of the nanoparticles, which often differ significantly from those of the bare nanoparticles . The protein adsorption on nanoparticles confers a new biological identity to the biological milieu, which subsequently controls the biological response of the nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…However, technological advancement continues to open alternate pathways to overcome this barrier. Nanotechnology and the use of nanoparticles have been extensively explored in recent years due to its wide range of practical application in physics, optics, electronics, and even medicine [ 82 , 83 ]. Nanoparticles can be defined as an ordered cluster of atoms, typically inorganic materials, that have at least one dimension between 1 and 10 nanometers.…”
Section: Nanotechnology In Protein Crystallographymentioning
confidence: 99%
“…Chen in 2017 described another approach for nucleation induction using nanodiamond (ND) carbon based particles. Like the gold particles described by Ko, NDs were modified with various oxygen containing groups including -COOH, -COH, and -C=O for protein conjugation [ 83 ]. Chen reported that the nanoparticles were able to increase the crystallization efficiency of several proteins including lysozyme, ribonuclease A, proteinase K, and catalase [ 83 ].…”
Section: Nanotechnology In Protein Crystallographymentioning
confidence: 99%
“…Different approaches facilitating the nucleation step have been proposed: (i) when an initial crystallization condition provides only poor quality crystals (e.g., urchin morphology or fine needles), homogeneous nucleation can be envisaged through seeding of crystallization drops with fragments of crystal. (ii) Second, heterologous nucleation relies on the introduction of materials within the drop at the start of the crystallization process. Various materials have been evaluated with more or less success. (iii) Finally, the recent development of molecular glues (calixarene, polyoxometalate, or lanthanide complexes) able to improve or mediate the protein–protein contacts is nowadays the most straightforward strategy to improve the nucleation step. Among these molecular glues, we introduced, in 2017, the crystallophore …”
Section: Introductionmentioning
confidence: 99%